2007
DOI: 10.1109/tasc.2007.897763
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Gaseous Helium Flow Cryogen in a Flexible Cryostat for Naval Applications of High Temperature Superconductors

Abstract: A fifty meter proof of concept demonstrator was developed utilizing gaseous helium as a cryogen for the use in a High Temperature Superconductor (HTS) based degaussing system for use on Navy ships. Increased signature requirements as Navy future missions move into littoral waters have resulted in a new copper degaussing system. This system has an increased weight and installation cost because of the additional copper cable required. High temperature superconductors have been suggested as a replacement to the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(11 citation statements)
references
References 1 publication
0
9
0
Order By: Relevance
“…However, the application of this cryogen is mainly limited to terrestrial or ground-based applications of ReBCO superconductors, due to the fact that its minimum operating temperature is 64 K under subcooled situation, below which temperature, it freezes. In order to achieve higher current carrying capacity and higher power density in superconducting equipment, much lower operating temperatures are required compared to 77 K LN2 temperature 37 . Gaseous helium (GHe) has the ability to work at lower cryogenic temperatures with a lower risk of suffocation compared with LN2.…”
Section: Iiib Liquid and Gaseous Insulationmentioning
confidence: 99%
“…However, the application of this cryogen is mainly limited to terrestrial or ground-based applications of ReBCO superconductors, due to the fact that its minimum operating temperature is 64 K under subcooled situation, below which temperature, it freezes. In order to achieve higher current carrying capacity and higher power density in superconducting equipment, much lower operating temperatures are required compared to 77 K LN2 temperature 37 . Gaseous helium (GHe) has the ability to work at lower cryogenic temperatures with a lower risk of suffocation compared with LN2.…”
Section: Iiib Liquid and Gaseous Insulationmentioning
confidence: 99%
“…One major reason to use helium gas is to avoid a phase change in the coolant allowing a much larger temperature gradient across the length of the cable [5]. Therefore, there is no phase change as the helium travels down the cryostat.…”
Section: A Hts Cable Cryogenic Cooling Systemmentioning
confidence: 99%
“…Results of this testing showed that it was possible to cool a long length of cryostat, but helium charge pressure and flow rate would have a great impact on the temperature distribution along the cable [3].…”
Section: B Fiscal Year 2005 Cryogenic Loopmentioning
confidence: 99%